(untitled) (Journal of the College of Basic Education, 2022)
In the present study, the scrap yards (located within the latitudes 33o 21’ 613” to 33o 21’ 290” North, and longitudes 44o 51’ 299” to 44o 50’ 904” East) at Al-Tuwaitha nuclear site were scanned for the period from January to February 2016 using hand-held radiation detectors with the intent of locating radioactive sources thrown within piles of scrap material. Only one 137Cs radioactive source has been found with an estimated activity of 6.3×108 Bq, which was found to be considerably less than the “dangerous quantity” D-value of 1×1011 Bq. Assessment of the potential radiological consequences arising from exposure to the source during normal conditions has been conducted using Rad Pro Calculator Version 3.26 (2009). The potential radiological dose arising from normal occupational exposure situation was estimated to be 139 mSv/y at 1 meter distance from the source, which was considerably higher than the occupational dose limit of 20 mSv/y recommended in the International Atomic Energy Agency (IAEA) GSR Part 3 (2014), indicating that this source must be removed and treated as radioactive waste.